2006
DOI: 10.2350/11-05-0130.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and Distribution of Eosinophils in the Gastrointestinal Tract of Children

Abstract: There are a lack of data on the quantity and location of eosinophils in the gastrointestinal tract of healthy individuals. Accordingly, we examined gastrointestinal biopsies obtained during endoscopic evaluation of pediatric patients. Biopsies were previously interpreted as having no diagnostic abnormality. The presence of extracellular eosinophil constituents and the quantity of eosinophils in atopic versus nonatopic individuals was determined. In the esophagus, eosinophils were present in only 2.7% of high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
196
4
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(234 citation statements)
references
References 22 publications
18
196
4
16
Order By: Relevance
“…While the normal esophagus is devoid of eosinophils, the rest of the gastrointestinal tract contains readily detectable eosinophils. [54] Thus, differentiation of EGID from the normal condition relies on several factors including (1) eosinophil quantification (and comparisons to normal values at each medical center); (2) the location of eosinophils (e.g. their presence in abnormal positions such as the intra-epithelial and intestinal crypt regions); (3) associated pathological abnormalities (e.g.…”
Section: Evaluation For Egidmentioning
confidence: 99%
“…While the normal esophagus is devoid of eosinophils, the rest of the gastrointestinal tract contains readily detectable eosinophils. [54] Thus, differentiation of EGID from the normal condition relies on several factors including (1) eosinophil quantification (and comparisons to normal values at each medical center); (2) the location of eosinophils (e.g. their presence in abnormal positions such as the intra-epithelial and intestinal crypt regions); (3) associated pathological abnormalities (e.g.…”
Section: Evaluation For Egidmentioning
confidence: 99%
“…A histological finding of eosinophil infiltration (six cells-high power field (HPF)) in the lamina propria was thought to be a useful threshold for diagnosis of food protein-induced proctocolitis (31,32). However, DeBrosse et al (33) recently described that eosinophils (mean 16-20 cells-HPF) were normally observed in the GI tract of control children, especially in the colon. Functional studies of eosinophilic GI disorders are lacking and much needed to understand the physiology and pathophysiological roles of eosinophils in the GI tract (34).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal mice have eosinophils located in similar regions and concentrations as observed in adult mice, providing evidence that eosinophil homing into the gastrointestinal tract occurs independent of endogenous flora [47]. In humans, the appendix, cecum and ascending colon contain the highest concentration of eosinophils in the gastrointestinal tract [48,49]. Interestingly, the number of eosinophils found in normal colon mucosa is influenced by geography, as there was a 35-fold increase in the number of eosinophils counted in colonic mucosal biopsy samples from asymptomatic patients in New Orleans compared to Boston [50].…”
Section: Migration Of Eosinophils Into the Intestinementioning
confidence: 97%